TRANSFORMASI PEMBELAJARAN SASTRA BAGI SISWA DI KAWASAN PESISIR MELALUI TEKNIK INFOGRAFIK INTERAKTIF DAN GAMIFIKASI BERBASIS AKAL IMITASI - Ayu Hidayanti Ali; Nuramila Nuramila; Argariawan Tamsil; Puspita Dian Agustin (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2026)
As a system that shapes the human resources of a nation, education is a crucial aspect that must be maintained in harmony with the development of the times. The rapid flow of technological advancement demands that teachers continuously develop innovations within classroom settings — including in literature learning. Through the study of literature, students’ character and critical thinking skills are refined. Moreover, cultural and historical values within society can be taught through literary education. The cultivation of these values can be realized through the interaction between students and teachers by utilizing technology. Based on this premise, the present study aims to describe the transformation of literature learning for students in coastal areas through the use of interactive infographic techniques and gamification based on Artificial Intelligence (AI). The method employed in this research is descriptive. The findings reveal that the transformation of literature learning through interactive infographic and AI-based gamification techniques not only enhances students’ learning motivation but also helps improve their understanding of the structure of fable texts.